Copper foil laminated plate and application thereof

By using copper foil with specific surface roughness and phosphorus content in printed circuit boards, combined with the adhesion layer and dielectric layer of non-perfluoro resin, the problem of long signal transmission distance and poor adhesion between resin and copper foil is solved. , realizes efficient high-frequency signal transmission and improved board performance.

CN119485905APending Publication Date: 2025-02-18TAIWAN UNION TECHNOLOGY CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311121816.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-11
Filing Date
2023-09-01
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the high-frequency signal transmission, the existing printed circuit boards have a problem that the signal transmission distance becomes longer, and the adhesion between the resin with low dielectric constant and low dielectric loss and the copper foil is poor.

Method used

Copper foil with a specific surface roughness and phosphorus content is used, and a non-perfluoro resin adhesive layer and a dielectric layer are combined to form a copper foil laminated plate to improve tear strength, heat resistance and anti-aging characteristics.

Benefits of technology

It realizes the stability of signal transmission distance in high-frequency signal transmission, and improves the tear strength, heat resistance and anti-aging characteristics of the copper foil laminated plate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119485905A_ABST
    Figure CN119485905A_ABST
Patent Text Reader

Abstract

The invention provides a copper foil laminated plate. The copper clad laminate includes: a dielectric layer; an adhesive layer disposed on at least one side of the dielectric layer and formed of an adhesive material including a non-perfluororesin; the dielectric layer is arranged on one side of the adhesive layer, the copper foil is provided with a first surface, the copper foil is arranged on the other side, opposite to the dielectric layer, of the adhesive layer, the first surface is adhered to the adhesive layer, the first surface has ten-point average roughness (Rz) smaller than 0.5 micrometer, and the phosphorus element content of the copper foil on the first surface is below 499 micrograms / dm < 2 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a copper foil laminate, more particularly to a copper foil laminate having specific roughness characteristics and phosphorus content. The present invention also relates to a printed circuit board made from the copper foil laminate. Background Art

[0002] Portable electronic products continue to move towards high functionality and must be able to process large amounts of information at high speeds. As a result, base station signals are also becoming more high-frequency, making printed circuit boards suitable for high-frequency applications more and more important. In order to transmit signals without reducing the quality of high-frequency signals, the industry is committed to reducing the high-frequency transmission loss of printed circuit boards.

[0003] The transmission loss of a printed circuit board can be mainly divided into two parts, one part comes from the conductor loss of the copper foil, and the other part comes from the dielectric loss of the insulating resin substrate. In order to reduce the dielectric loss of the insulating resin substrate, thermoplastic resins (such as liquid crystal polymer resins or fluororesins) and thermosetting resins (such as polyphenylene ether resins) with low dielectric constants and low dielectric losses are often used on the market. However, it is known that resins with low dielectric constants and low dielectric losses often have the problem of poor adhesion to copper foil.

[0004] The reason for the above-mentioned problem is that most low-dielectric resins are resins with low polarity and molecular structures that are difficult to produce oriented polarization, which leads to the weakening of the intermolecular force at the interface between the insulating resin substrate and the copper foil, making it difficult to obtain chemical adhesion. In order to increase the adhesion at the interface between the insulating resin substrate and the copper foil, the prior art has a roughening treatment of providing a shape that can exert an anchoring effect on the surface of the copper foil, such as the "attachment of fine copper particles" disclosed in JP H05-029740 or the "formation of concave and convex by etching" disclosed in JP 2000-282265A. However, during signal transmission, the depth of the signal will become shallower as the frequency increases and it is easy to transmit near the surface of the copper foil (that is, the "skin effect"). Therefore, if the surface of the copper foil is subjected to the above-mentioned surface roughening treatment, the signal will flow along the concave and convex surface of the copper foil, resulting in a longer signal transmission distance.

[0005] In order to solve the problem of longer signal transmission distance, the prior art improves by reducing the conductor resistance of the copper foil, such as reducing the surface roughness of the original copper foil surface, or reducing the degree of roughening treatment. However, reducing the degree of roughening treatment will reduce the anchoring effect, resulting in a decrease in the physical adhesion of the interface between the insulating resin substrate and the copper foil.

[0006] Although the prior art uses an adhesive layer between the insulating resin substrate and the copper foil to try to solve the adhesion problem, it still cannot provide a high-frequency copper foil base board with both adhesion and dielectric properties. Summary of the invention

[0007] In view of the above technical problems, the present invention provides a copper foil laminate, which comprises a copper foil having a specific surface roughness and a specific phosphorus content, an adhesive layer comprising a non-perfluoro resin, and a dielectric layer, wherein the first surface having a specific surface roughness and a specific phosphorus content is a surface where the copper foil and the adhesive layer are in contact. The copper foil laminate of the present invention can have good tear strength, heat resistance and anti-aging properties, and is particularly suitable for high-frequency signal transmission.

[0008] Therefore, an object of the present invention is to provide a copper foil laminate, comprising:

[0009] Dielectric layer;

[0010] an adhesive layer disposed on at least one side of the dielectric layer and formed of an adhesive material including a non-perfluorinated resin; and

[0011] A copper foil having a first surface, the copper foil is disposed on the other side of the adhesive layer opposite to the dielectric layer, and is adhered to the adhesive layer with the first surface.

[0012] The first surface has a ten-point average roughness (Rz) of less than 0.5 micrometers, and the phosphorus content of the copper foil at the first surface is 499 micrograms / square decimeter (μg / dm 2 )the following.

[0013] In some embodiments of the present invention, the fluorine atom content of the non-perfluororesin is 60% or less based on the total number of atoms in the repeating unit.

[0014] In some embodiments of the present invention, the phosphorus content of the copper foil at the first surface is 199 μg / dm 2 the following.

[0015] In some embodiments of the present invention, the non-perfluorinated resin is selected from the following group: polychlorotrifluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, ethylene-tetrafluoroethylene copolymer, ethylene-chlorotrifluoroethylene copolymer, and combinations thereof.

[0016] In some embodiments of the present invention, the dielectric layer comprises a dielectric material formed from a resin composition.

[0017] In some embodiments of the present invention, the resin composition comprises a thermosetting resin selected from the following group: epoxy resin, thermosetting phenolic resin having a reactive functional group, thermosetting benzoxazine resin, thermosetting polyphenylene ether resin, and combinations thereof.

[0018] In some embodiments of the present invention, the resin composition comprises a thermoplastic resin selected from the following groups: perfluorinated resin, liquid crystal polymer, and combinations thereof. The perfluorinated resin may be selected from the following groups: polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and combinations thereof.

[0019] In some embodiments of the present invention, the resin composition further comprises a component selected from the following group: a catalyst, an elastomer, a filler, a dispersant, a toughening agent, a viscosity modifier, a flame retardant, a plasticizer, a coupling agent, and a combination thereof.

[0020] Another object of the present invention is to provide a printed circuit board, which is made of the copper foil laminate as described above.

[0021] In order to make the above-mentioned objectives, technical features and advantages of the present invention more obvious and easy to understand, some specific implementation schemes are described in detail below. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a schematic cross-sectional view of a copper foil laminate according to one embodiment of the present invention.

[0023] Description of Reference Numerals

[0024] 1: Copper foil laminate

[0025] 2,6: Copper foil

[0026] 3,5: Adhesion layer

[0027] 4: Dielectric layer. DETAILED DESCRIPTION

[0028] Some specific embodiments according to the present invention will be described in detail below; however, the present invention can also be practiced in a variety of different forms, and the protection scope of the present invention should not be limited to the specific embodiments.

[0029] Unless otherwise specified, the terms "a", "an", "the" and similar terms used in the specification and claims should be understood to include both the singular and the plural.

[0030] Unless otherwise specified, the terms “first”, “second” and the like used in the specification and the claims are merely used to distinguish the described elements or components and have no special meanings and are not used to represent a sequence.

[0031] Unless otherwise stated, when describing the components contained in the solution, mixture, composition, or glue in this specification and claims, the weight of the solvent is not included in the calculation.

[0032] Unless otherwise specified, in this specification and claims, the term "fluorine atom content" refers to the number percentage of fluorine atoms in a repeating unit in a fluororesin, calculated based on the total number of all atoms in the repeating unit, and the unit is %.

[0033] Herein, the term "perfluororesin" refers to a fluorocarbon polymer having a fluorine atom content of more than 60%. The term "non-perfluororesin" refers to a fluorocarbon polymer having a fluorine atom content of less than 60%.

[0034] Herein, the material of "copper foil" is pure copper having a purity of 99.5% or more.

[0035] The copper foil laminate of the present invention can obtain improved tear strength, heat resistance and anti-aging properties by combining a copper foil having a specific surface roughness and a specific phosphorus content on the first surface (the surface in contact with the adhesive layer), an adhesive layer containing a non-perfluoro resin, and a dielectric layer. The following provides a detailed description of the copper foil laminate of the present invention and its related applications.

[0036] 1. Copper foil laminate

[0037] The copper foil laminate of the present invention comprises a dielectric layer, an adhesive layer disposed on at least one side of the dielectric layer, and a copper foil disposed on the other side of the adhesive layer opposite to the dielectric layer. In some embodiments of the present invention, the copper foil laminate is substantially composed of the dielectric layer, the adhesive layer, and the copper foil, or is composed of the dielectric layer, the adhesive layer, and the copper foil.

[0038] Figure 1 The figure shows a schematic cross-sectional view of a copper foil laminate according to an embodiment of the present invention, wherein the copper foil laminate 1 comprises a dielectric layer 4, an adhesive layer 3 and an adhesive layer 5 respectively arranged on both sides of the dielectric layer, and a copper foil 2 and a copper foil 6 respectively arranged on the other side of the adhesive layer opposite to the dielectric layer.

[0039] 1.1. Dielectric layer

[0040] The dielectric layer comprises a dielectric material formed of a resin composition, or is substantially composed of the dielectric material, or is composed of the dielectric material. The dielectric material can be obtained by drying the resin composition and forming it into a resin sheet. The method for preparing the resin sheet is not particularly limited, and can be any existing method for preparing a resin sheet in the technical field to which the present invention belongs. For example, a gelatinous mass or slurry of the resin composition can be prepared first, and then the gelatinous mass or slurry of the resin composition can be formed into a sheet by roller forming, coating, die casting, or melt extrusion and roller forming. Thereafter, the sheet is dried at, for example, 90°C to 170°C for 1 hour to 5 hours to remove the solvent. The dried sheet is sequentially subjected to calendering and sintering treatment to obtain a resin sheet. The calendering temperature can be 90°C to 150°C, the sintering temperature can be 300°C to 400°C, and the sintering time can be 20 minutes to 60 minutes.

[0041] The resin sheet can also be prepared as follows. First, prepare a pellet or slurry of a resin composition. Next, dry the pellet or slurry of the resin composition at, for example, 80° C. to 120° C. for 1 to 5 hours to remove the solvent. Thereafter, the dried pellet or slurry is formed into a sheet at 90° C. to 150° C. by roll forming, die casting, or melt extrusion and roll forming. Finally, dry the sheet at 150° C. to 300° C. for 120 to 240 minutes to obtain a resin sheet.

[0042] In some embodiments of the present invention, the resin sheet may include one or more reinforcing materials. The resin sheet including the reinforcing material may be prepared by impregnating or coating the reinforcing material with a resin composition and drying the impregnated or coated reinforcing material. The impregnation or coating method includes but is not limited to dipping, roller coating, die coating, rod coating, and spraying. The drying condition may be drying at 200°C to 600°C for 1 minute to 30 minutes.

[0043] There is no particular limitation on the type of reinforcing material, and it can be any existing reinforcing material in the technical field to which the present invention belongs. In general, the material of the reinforcing material includes, but is not limited to, fibers selected from the following groups: glass fibers, inorganic fibers other than glass fibers, and organic fibers. Examples of glass fibers include, but are not limited to, E-glass fibers (E-glass), NE-glass fibers (NE-glass), S-glass fibers (S-glass), L-glass fibers (L-glass), D-glass fibers (D-glass), T-glass fibers (T-glass), Q-glass fibers (Q-glass), UN-glass fibers (UN-glass), and spherical glass. Examples of inorganic fibers other than glass fibers include, but are not limited to, quartz fibers. Examples of organic fibers include, but are not limited to, polyimide, polyamide, polyester, liquid crystal polyester, and polytetrafluoroethylene. The form of the reinforcing material includes, but is not limited to, woven fabrics, non-woven fabrics, rovings, chopped strands of felt, and surface felts. Based on the viewpoint of dimensional stability, it is preferred to use woven fabrics that have been subjected to super fiber opening treatment and filling treatment as reinforcing materials. From the viewpoint of moisture absorption and heat resistance, it is preferred to use glass fiber woven fabrics that have been surface treated by epoxy silane treatment, silane coupling agent treatment, etc. as reinforcement. From the viewpoint of electrical properties, it is preferred to use low-dielectric glass fiber cloth as reinforcement, and examples of the low-dielectric glass fiber cloth include glass fiber cloth composed of glass fibers such as L-glass, NE-glass, and Q-glass.

[0044] The thickness of the dielectric layer is not particularly limited. Generally speaking, the thickness of the dielectric layer may be less than 310 μm, preferably 250 μm to 310 μm, such as 250 μm, 251 μm, 252 μm, 253 μm, 254 μm, 255 μm, 256 μm, 257 μm, 258 μm, 259 μm, 260 μm, 261 μm, 262 μm, 263 μm, 264 μm, 265 μm, 266 μm, 267 μm, 268 μm, 269 μm, 270 μm, 271 μm, 272 μm, 273 μm, 274 μm, 275 μm, 276 μm, 277 μm, 278 μm , 279 μm, 280 μm, 281 μm, 282 μm, 283 μm, 284 μm, 285 μm, 286 μm, 287 μm, 288 μm, 289 μm, 290 μm, 291 μm, 292 μm, 293 μm, 294 μm, 295 μm, 296 μm, 297 μm, 298 μm, 299 μm, 300 μm, 301 μm, 302 μm, 303 μm, 304 μm, 305 μm, 306 μm, 307 μm, 308 μm, 309 μm, or 310 μm, or a range consisting of any two of the above values.

[0045] 1.1.1. Resin composition

[0046] The resin composition used to form the dielectric material may include a thermosetting resin or a thermoplastic resin. When the resin composition includes a thermosetting resin, it is also referred to as a thermosetting resin composition. When the resin composition includes a thermoplastic resin, it is also referred to as a thermoplastic resin composition. In addition, the resin composition used to form the dielectric material may also include additives as needed to adaptably improve the processability of the resin composition during the preparation process, or to improve the physicochemical properties of the obtained electronic material.

[0047] 1.1.1.1. Thermosetting resin

[0048] Thermosetting resin refers to a component that can form a network structure and gradually solidify through a cross-linking reaction after being heated. Examples of thermosetting resins include, but are not limited to, epoxy resins, thermosetting phenolic resins with reactive functional groups, thermosetting benzoxazine resins, and thermosetting polyphenylene ether resins. Each of the aforementioned thermosetting resins can be used alone or in combination. Herein, reactive functional groups refer to any functional groups that can react with other groups to solidify. Examples of reactive functional groups include, but are not limited to, hydroxyl, carboxyl, alkenyl, and amine groups. In some embodiments of the present invention, epoxy resins, thermosetting polyphenylene ether resins, or a combination thereof are used as thermosetting resins.

[0049] Herein, epoxy resin refers to a thermosetting resin having at least two epoxy functional groups in one molecule, such as a multifunctional epoxy resin and a linear phenolic epoxy resin. Examples of multifunctional epoxy resins include, but are not limited to, difunctional epoxy resins, tetrafunctional epoxy resins, and octafunctional epoxy resins. There is no particular limitation on the type of epoxy resin that can be used to form dielectric materials, and a person skilled in the art of the present invention can select according to actual needs after reading the specification of this case. For example, based on the flame retardant properties of the resin composition, a phosphorus-containing or bromine-containing epoxy resin can be used, and a halogen-free epoxy resin can also be used in response to halogen-free environmental protection requirements.

[0050] Examples of the epoxy resin include, but are not limited to, dicyclopentdiene (DCPD) type epoxy resin, bisphenol type epoxy resin, novolac type epoxy resin, distyrene type epoxy resin, epoxy resin containing triazine (triazine) skeleton, epoxy resin containing fluorene skeleton, trisphenol methane type epoxy resin, biphenyl type epoxy resin, xylylene type epoxy resin, biphenyl aralkyl type epoxy resin, naphthalene type epoxy resin, and alicyclic epoxy resin. Examples of bisphenol type epoxy resin include, but are not limited to, bisphenol A type epoxy resin, bisphenol F type epoxy resin, and bisphenol S type epoxy resin. Examples of novolac type epoxy resin include, but are not limited to, phenol novolac type epoxy resin, cresol novolac type epoxy resin, bisphenol A novolac type epoxy resin, and bisphenol F novolac type epoxy resin. Other examples of epoxy resins also include diglycidyl ether compounds of polycyclic aromatics such as polyfunctional phenols and anthracene. Examples of phosphorus-containing epoxy resins include, but are not limited to, epoxy resins modified with 9,10-dihydro-9-oxa-10-phosphahenanthrene-10-oxide (9,10-dihydro-9-oxa-10-phosphahenanthrene-10-oxide, DOPO). Examples of bromine-containing epoxy resins include, but are not limited to, tetrabromobisphenol A type epoxy resins. The aforementioned epoxy resins may be used alone or in combination. In the following examples, a phenolic epoxy resin is used.

[0051] The amount of epoxy resin used can be adjusted according to actual needs. For example, based on the total weight of the resin composition, the content of the epoxy resin can be 10 wt % to 50 wt %, such as 10 wt %, 15 wt %, 20 wt %, 25 wt %, 30 wt %, 35 wt %, 40 wt %, 45 wt %, or 50 wt %, or a range between any two of the above values.

[0052] In this article, thermosetting polyphenylene ether resin refers to a thermosetting polyphenylene ether resin having at least one repeating unit in the main chain of the molecule. And a resin having an unsaturated group at the end, wherein R is independently H or a C1 to C5 alkyl group, and v is an integer from 1 to 100. The unsaturated group refers to a group that can undergo addition polymerization with other components having unsaturated groups, and the addition polymerization reaction can be initiated by light or heat in the presence of a polymerization initiator. Examples of unsaturated groups include, but are not limited to, vinyl, vinyl benzyl, allyl, acrylic, and methacrylic. Examples of thermosetting polyphenylene ether resins include, but are not limited to, vinyl-containing polyphenylene ether resins, allyl-containing polyphenylene ether resins, vinyl benzyl-containing polyphenylene ether resins, acrylic-containing polyphenylene ether resins, and methacrylic-containing polyphenylene ether resins. The aforementioned polyphenylene ether resins can be used alone or in combination.

[0053] The preparation method of the thermosetting polyphenylene ether resin is not the technical focus of the present invention, and can be performed by a person skilled in the art based on the disclosure of this specification and the common knowledge possessed, and will not be elaborated here. Literature related to the preparation method of the thermosetting polyphenylene ether resin can be listed in US 6,995,195 B2 (polyphenylene ether resin containing vinylbenzyl group), US 5,218,030 A (polyphenylene ether resin containing allyl group), US 5,352,745 A (polyphenylene ether resin containing methacrylate group), US 6,352,782 B2, and US2016 / 0280913 A1, and the entire texts of these documents are hereby incorporated by reference.

[0054] In some embodiments of the present invention, the resin composition comprises a thermosetting polyphenylene ether resin having a structure represented by the following formula (I):

[0055]

[0056] In formula (I), R3, R4, R5, and R6 are each independently H, or a C1 to C5 alkyl group which may or may not be substituted; m and n are each independently an integer from 0 to 100, provided that m and n are not simultaneously 0; Z is absent, -O-, or aryl, wherein R7 and R8 are each independently H or C1 to C12 alkyl; X and Y are each independently absent, a carbonyl group, or a group having an alkenyl group; and A1 and A2 are each independently

[0057] In a preferred embodiment of the present invention, R3, R4, R5, and R6 of formula (I) are -CH3, and Z is X and Y do not exist, and A1 and A2 are independent of each other.

[0058] In general, the weight average molecular weight (Mw) of the thermosetting polyphenylene ether resin may be 1000 to 50000, preferably 1000 to 10000, and more preferably 1000 to 5000. Examples of commercially available thermosetting polyphenylene ether resins include products with the model OPE-2St 1200 or OPE-2st 2200 available from MITSUBISHI GAS CHEMICAL, products with the model SA-9000 available from SABIC, products with the model PP807 available from Shinichi Chemical, and polyphenylene ether products available from ASAHI KASEI. From the viewpoint of high frequency applications, it is preferred to use thermosetting polyphenylene ether resins to form dielectric materials.

[0059] The amount of the thermosetting polyphenylene ether resin can be adjusted according to actual needs without special restrictions. For example, based on the total weight of the resin composition, the content of the thermosetting polyphenylene ether resin can be 15 wt % to 60 wt %, such as 15 wt %, 20 wt %, 25 wt %, 30 wt %, 35 wt %, 40 wt %, 45 wt %, 50 wt %, 55 wt %, or 60 wt %, or a range between any two of the above values.

[0060] 1.1.1.2. Thermoplastic resin

[0061] The characteristic of thermoplastic resins is that they soften when heated or harden when cooled. Examples of thermoplastic resins include, but are not limited to, perfluororesins and liquid crystal polymers. Each of the aforementioned thermoplastic resins may be used alone or in combination.

[0062] Herein, perfluororesin refers to a fluorocarbon polymer having a fluorine atom content of more than 60%. Examples of perfluororesins include, but are not limited to, polytetrafluoroethylene (PTFE, fluorine atom content of 66.7%), polyfluoroalkoxy alkane (PFA, fluorine atom content of 66.7%), and fluorinated ethylene propylene copolymer (FEP, fluorine atom content of 66.7%). In the following examples, PTFE is used as the thermoplastic resin.

[0063] Commercially available products of perfluororesins suitable for the present invention include, but are not limited to: D210 (solid content 60%) available from Daikin; Teflon (Teflon 6000) available from Dupont; TM PTFE DISP 30LX product (solid content 60%); Algoflon D 3511F product available from Solvay (solid content 59%); AD9300 product (solid content is 60%); and Dyneon available from 3M TM TF5050Z product (solid content 58%) From the viewpoint of high frequency application, it is preferable to use perfluororesin to form the dielectric material.

[0064] The amount of the perfluororesin used can be adjusted according to actual needs and is not particularly limited. For example, based on the total weight of the resin composition, the content of the perfluororesin can be 30% to 90% by weight, such as 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, or 90% by weight, or a range between any two of the above values.

[0065] 1.1.1.3. Additives

[0066] Examples of additives that can be used in dielectric materials include, but are not limited to, catalysts, elastomers, fillers, dispersants, toughening agents, viscosity modifiers, flame retardants, plasticizers, and coupling agents. The aforementioned additives can be used alone or in combination.

[0067] 1.1.1.3.1. Hardener

[0068] When the resin composition includes a thermosetting resin, a hardener may be further added as needed to increase the degree of crosslinking. Herein, a hardener refers to a component having an unsaturated functional group and capable of undergoing a crosslinking reaction with other components having unsaturated functional groups (e.g., epoxy resin or thermosetting polyphenylene ether resin) to form a three-dimensional network structure. The type of hardener that can be used in the present invention is not particularly limited, as long as it can increase the degree of crosslinking.

[0069] In some embodiments of the present invention, when the resin composition includes an epoxy resin, suitable hardeners include, but are not limited to, -OH-containing compounds, amine-containing compounds, anhydride compounds, and active ester compounds. Each of the aforementioned hardeners may be used alone or in combination. Specific examples of hardeners include, but are not limited to, phenolic resin (PN resin), styrene maleic anhydride copolymer (SMA copolymer), bismaleimide (BMI), dicyandiamide (Dicy), 4,4'-diaminodiphenyl sulfone (DDS), di(anilino)methane, aromatic diamines, aromatic dianhydrides, aliphatic dianhydrides, triazine, cyanate ester resin (CE), triazaphenol resin, benzoxazine resin and its ring-opening polymer, and styrene and vinylphenol copolymer. In the following examples, Dicy or BMI is used.

[0070] In some embodiments of the present invention, when the resin composition comprises a thermosetting polyphenylene ether resin, a hardener selected from the following group can be used: BMI, an elastomer containing butadiene and / or styrene, an isocyanurate containing vinyl and / or allyl groups, and combinations thereof. In the following examples, an isocyanurate containing allyl groups is used.

[0071] The amount of the hardener can be adjusted according to actual needs. Generally speaking, based on the total weight of the resin composition, the content of the hardener can be 15 wt % to 65 wt %, such as 15 wt %, 20 wt %, 25 wt %, 30 wt %, 35 wt %, 40 wt %, 45 wt %, 50 wt %, 55 wt %, 60 wt %, or 65 wt %, or a range between any two of the above values.

[0072] 1.1.1.3.2. Catalyst

[0073] When the resin composition includes a thermosetting resin, a hardener may be further added as needed to promote the curing reaction. Herein, the catalyst refers to a component that can promote the curing reaction, such as promoting the ring-opening reaction of the epoxy functional group and reducing the curing reaction temperature of the resin composition.

[0074] The type of catalyst that can be used in the present invention is not particularly limited, as long as it can promote the curing reaction. Suitable catalysts include, but are not limited to, organic peroxides, tertiary amines, quaternary ammonium, imidazole compounds, and pyridine compounds. Examples of organic peroxides include, but are not limited to, dibenzoyl peroxide (benzoyl peroxide, BPO), dicumyl peroxide (dicumyl peroxide, DCP), and α,α'-bis (tertiary butyl peroxy) diisopropyl benzene (α,α'-bis (t-butylperoxy) diisopropyl benzene). Examples of tertiary amines include, but are not limited to, dimethylbenzylamine, 2-(dimethylaminomethyl)phenol, and 2,4,6-tris (dimethylaminomethyl)phenol. Examples of imidazole compounds include, but are not limited to, 2-methylimidazole, 2-ethyl-4-methylimidazole, and 2-phenylimidazole. Examples of pyridine compounds include, but are not limited to, 2,3-diaminopyridine, 2,5-diaminopyridine, 2,6-diaminopyridine, 4-dimethylaminopyridine, 2-amino-3-methylpyridine, 2-amino-4-methylpyridine, and 2-amino-3-nitropyridine. The aforementioned catalysts may be used alone or in combination.

[0075] When the resin composition includes an epoxy resin, the catalyst is preferably selected from tertiary amines, quaternary ammoniums, imidazole compounds, and pyridine compounds. In the following examples, 2-methylimidazole is used as a catalyst for epoxy resin. When the resin composition includes a thermosetting polyphenylene ether resin, the catalyst is preferably selected from an organic peroxide. In the following examples, α,α'-bis(tertiary butylperoxy)diisopropylbenzene is used as a catalyst for thermosetting polyphenylene ether resin.

[0076] The amount of the catalyst can be adjusted according to actual needs and is not particularly limited. For example, based on the total weight of the resin composition, the content of the catalyst can be 10 ppm to 2 weight %, such as 10 ppm, 50 ppm, 100 ppm, 500 ppm, 0.1 weight %, 0.5 weight %, 1 weight %, 1.5 weight %, or 2 weight %, or a range between any two of the above values.

[0077] 1.1.1.3.3. Flame retardants

[0078] The resin composition may further contain a flame retardant as needed to improve the heat resistance and flame retardancy of the electronic material. The types of flame retardants include but are not limited to phosphorus-containing flame retardants, bromine-containing flame retardants, and nitrogen-containing compounds, and each type of flame retardant can be used alone or in any combination.

[0079] Examples of phosphorus-containing flame retardants include, but are not limited to, phosphate esters, phosphazenes, ammonium polyphosphate, metal phosphinates, and melamine phosphate. Each of the above phosphorus-containing flame retardants can be used alone or in combination.

[0080] Examples of bromine-containing flame retardants include, but are not limited to, tetrabromobisphenol A, decabromodiphenyl oxide, decabrominated diphenylethane, 1,2-bis(tribromophenyl)ethane, brominated epoxy oligomer, octabromotrimethylphenylindane, bis(2,3-dibromopropyl ether), tris(tribromophenyl)triazine, brominated aliphatic hydrocarbon, and brominated aromatic hydrocarbon. Each of the above-mentioned bromine-containing flame retardants may be used alone or in combination. Examples of nitrogen-containing compounds include, but are not limited to, melamine and its derivatives. Commercially available phosphorus-containing flame retardants include the product available under the designation Melapur 200 from BASF.

[0081] The amount of the flame retardant can be adjusted according to actual needs and is not particularly limited. For example, based on the total weight of the resin composition, the content of the flame retardant can be 0 wt % to 30 wt %, such as 0 wt %, 1 wt %, 5 wt %, 10 wt %, 15 wt %, 20 wt %, 25 wt %, or 30 wt %, or a range between any two of the above values.

[0082] 1.1.1.3.4. Filling

[0083] The resin composition may further include fillers as needed to improve mechanical strength, thermal conductivity and dimensional stability. Examples of suitable fillers include, but are not limited to, fillers selected from the following groups: silica (including hollow silica), alumina, magnesium oxide, magnesium hydroxide, calcium carbonate, talc, clay, aluminum nitride, boron nitride, aluminum hydroxide, aluminum silicon carbide, silicon carbide, sodium carbonate, titanium dioxide, zinc oxide, zirconium oxide, quartz, diamond, diamondoid, graphite, calcined kaolin, bailing clay, mica, hydrotalcite, PTFE powder, glass beads, ceramic whiskers, nano carbon tubes, and nano inorganic powders. In the attached examples, silica is used as a filler.

[0084] The amount of filler can be adjusted according to actual needs without special restrictions. For example, based on the total weight of the resin composition, the content of the filler can be 0% by weight to 60% by weight, such as 0%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, or 60% by weight, or a range between any two of the above values.

[0085] 1.1.2. Preparation of resin composition

[0086] Regarding the preparation of the thermosetting resin composition, the components of the thermosetting resin composition, including the thermosetting resin and optional additives, can be uniformly mixed with a stirrer and dissolved or dispersed in a solvent to form a slurry, a colloidal group, or a varnish for subsequent processing. The solvent can be any inert solvent that can dissolve or disperse the components of the thermosetting resin composition but does not react with these components. For example, the solvents that can be used to dissolve or disperse the components of the thermosetting resin composition include but are not limited to: toluene, γ-butyrolactone, methyl ethyl ketone, cyclohexanone, butanone, acetone, xylene, methyl isobutyl ketone, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), and N-methylpyrolidone (NMP). The aforementioned solvents can be used alone or in combination. The amount of solvent used is not particularly limited, in principle, as long as the components of the resin composition can be uniformly dissolved or dispersed therein. In the following examples, methyl ethyl ketone is used as the solvent.

[0087] Regarding the preparation of the thermoplastic resin composition, when the thermoplastic resin is solid, the aforementioned preparation method for the thermosetting resin composition can be referred to, but a solvent selected from the following group is used: water, ethanol, isopropanol, acetone, and combinations thereof. When the thermoplastic resin is in the form of a suspension, as long as the solvent content in the suspension is sufficient, the suspension of the thermoplastic resin can be directly mixed with the necessary additives by a stirrer to obtain a slurry or agglomerate without the need for additional solvent.

[0088] 1.2. Adhesion layer

[0089] The inventor of the present invention has found that when a perfluororesin layer is used as an adhesive layer between the copper foil and the dielectric layer, during the heat pressing of the laminate, the phosphorus element released from the surface of the copper foil in contact with the adhesive layer will react with the functional groups of the perfluororesin in the adhesive layer, causing the chemical bonds of the molecular chains in the perfluororesin to break, thereby reducing the adhesion (tear strength) between the adhesive layer and the copper foil. Therefore, the adhesive layer in the copper foil laminate of the present invention is formed by an adhesive material containing a non-perfluororesin, and preferably does not contain a perfluororesin.

[0090] The non-perfluororesin refers to a fluorocarbon polymer having a fluorine atom content of less than 60%. Specific examples of non-perfluororesins include, but are not limited to, polychlorotrifluoroethylene (PCTFE, fluorine atom content of 50%), polyvinylidene difluoride (PVDF, fluorine atom content of 33.3%), polyvinyl fluoride (PVF, fluorine atom content of 16.7%), ethylene-tetrafluoroethylene copolymer (ETFE copolymer, fluorine atom content of 33.3%), and ethylene-chloro trifluoroethylene copolymer (ECTFE copolymer, fluorine atom content of 25%).

[0091] The non-perfluororesin may also be a modified non-perfluororesin obtained by subjecting a perfluororesin to a plasma or chemical agent treatment. Commercially available modified non-perfluororesins include, but are not limited to, products with model GK-570 (fluorine atom content of 24.4%) and model SE-405 (fluorine atom content of 24.4%) available from Daikin. The amount of the non-perfluororesin may be adjusted according to actual needs. Generally speaking, based on the total weight of the adhesive material, the content of the non-perfluororesin may be 80% to 95% by weight, such as 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, or 95% by weight, or a range between any two of the above values.

[0092] The adhesive material may further include a surfactant as needed to adaptably improve the interfacial properties of the adhesive material. Examples of the surfactant include, but are not limited to, fluorine-based surfactants. Examples of fluorine-based surfactants include, but are not limited to, perfluorobutanoic acid (PFBA), perfluoropentanoic acid (PFPA), perfluorohexanoic acid (PFHxA), perfluoroheptanoic acid (PFHpA), perfluorooctanoic acid (PFOA), perfluorononanoic acid (PFNA), perfluorodecanoic acid (PFDA), perfluorobutanesulfonamide (H-FBSA), perfluorooctanesulfonamide (PFOSA), perfluorohexanesulfonic acid (PFHxS), and perfluorooctanesulfonic acid (PFOS). The amount of the surfactant can be adjusted according to actual needs without special restrictions. For example, based on the total weight of the adhesive material, the content of the surfactant can be 5% to 20% by weight, such as 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, or a range between any two of the above values.

[0093] Regarding the preparation of the adhesive material, the non-perfluororesin and the optional surfactant can be uniformly mixed with a stirrer and dissolved or dispersed in a solvent, and stirred at a speed of 500 rpm to 1000 rpm for 10 minutes to 30 minutes as needed. There is no special restriction on the amount of solvent used, in principle, as long as the components of the adhesive material can be uniformly dissolved or dispersed therein. Examples of solvents that can be used to dissolve or disperse the components of the adhesive material include but are not limited to: water, toluene, ethanol, isopropanol, and acetone. The aforementioned solvents can be used alone or in combination. In the attached embodiments, water or toluene is used as a solvent.

[0094] The adhesive material can be formed into an adhesive layer by an existing forming method in the technical field to which the present invention belongs. In some embodiments of the present invention, the adhesive material is coated on the copper foil and dried in such a way that the thickness of the adhesive layer after drying becomes a specific value to obtain a copper foil with an adhesive layer. The coating method is not particularly limited, for example, it can be gravure coating, die coating, or doctor blade coating. In addition, a scraper or rod coater can also be used for coating. In addition, in some embodiments of the present invention, after the adhesive material is coated on the surface of the copper foil, the copper foil coated with the adhesive material is sintered at a temperature of 300°C to 400°C for 15 minutes to 60 minutes to obtain a copper foil with an adhesive layer.

[0095] The thickness of the adhesive layer is not particularly limited, but is preferably between 5 μm and 15 μm, for example, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or a range formed by any two of the above values.

[0096] 1.3. Copper foil

[0097] The copper foil of the present invention has a first surface and is adhered to the adhesive layer with the first surface, wherein the first surface has a ten-point average roughness (Rz) of less than 0.5 micrometers, and the phosphorus content of the copper foil at the first surface is 499 μg / dm 2 In some embodiments of the present invention, the copper foil is a copper foil that has not been subjected to surface roughening treatment.

[0098] 1.3.1. Types and materials of copper foil

[0099] In the past, the copper foil used for rigid substrates was electrolytic copper foil, and the copper foil used for flexible substrates was rolled copper foil. However, with the development of flexible substrates, electrolytic copper foils with similar properties to rolled copper foils have been developed. Therefore, the type of copper foil that can be used for the copper foil laminate of the present invention is not particularly limited, and can be any type of copper foil, including electrolytic copper foil and rolled copper foil.

[0100] Electrolytic copper foil is usually produced by electrolyzing copper from a copper sulfate plating bath and depositing it on a titanium or stainless steel roller. Rolled copper foil is usually produced by repeatedly plastic working and heat treating a copper ingot using a rolling roller. The materials of copper foil include, but are not limited to: refined copper (JIS H3100 alloy number C 1100), oxygen-free copper (JIS H3100 alloy number C1020 or JIS H3510 alloy number C1011), phosphorus deoxidized copper (JIS H3100 alloy number C 1201, C1220 or C 1221), electrolytic copper, Sn-doped copper, Ag-doped copper, Cr-added copper alloy, Zr-added copper alloy, Mg-added copper alloy, and corson copper alloys added with Ni and Si. In addition, the copper foil may contain 30 ppm to 300 ppm of one or more elements selected from the following group as needed: P, B, Ti, Mn, V, Cr, Mo, Ag, Sn, In, Au, Pd, Zn, Ni, Si, Zr, and Mg.

[0101] In addition, in order to improve the anti-rust ability, dielectric properties, heat resistance, chemical resistance of the copper foil and improve the adhesion between the copper foil and the dielectric material, the copper foil may be subjected to appropriate surface treatment. The surface treatment includes but is not limited to roughening treatment, heat resistance treatment, anti-rust treatment, chromate treatment, and silane coupling treatment. In some embodiments of the present invention, the copper foil may be subjected to one or more of the above surface treatments, as long as the first surface of the copper foil after the surface treatment still has a ten-point average roughness (Rz) of less than 0.5 microns and a surface roughness of 499 μg / dm 2 The following phosphorus content is sufficient.

[0102] 1.3.2. Properties of copper foil

[0103] The first surface of the copper foil of the present invention has a ten-point average roughness (Rz) of less than 0.5 micrometers, and the Rz is measured according to the standard of JIS B0601:2001 using a contact surface roughness tester, and the diameter of the probe used is 2 micrometers. The Rz of the first surface of the copper foil of the present invention can be 0.49 micrometers, 0.48 micrometers, 0.47 micrometers, 0.46 micrometers, 0.45 micrometers, 0.44 micrometers, 0.43 micrometers, 0.42 micrometers, 0.41 micrometers, 0.40 micrometers, 0.39 micrometers, 0.38 micrometers, 0.37 micrometers, 0.36 micrometers, 0.35 micrometers, 0.34 micrometers, 0.33 micrometers, 0.32 micrometers, 0.31 micrometers, 0.30 micrometers, 0.29 micrometers, 0.28 micrometers, 0.27 micrometers, 0.26 micrometers, 0.25 micrometers, 0.24 micrometer, 0.23 micrometer, 0.22 micrometer, 0.21 micrometer, 0.20 micrometer, 0.19 micrometer, 0.18 micrometer, 0.17 micrometer, 0.16 micrometer, 0.15 micrometer, 0.14 micrometer, 0.13 micrometer, 0.12 micrometer, 0.11 micrometer, 0.10 micrometer, 0.09 micrometer, 0.08 micrometer, 0.07 micrometer, 0.06 micrometer, 0.05 micrometer, 0.04 micrometer, 0.03 micrometer, 0.02 micrometer, 0.01 micrometer, or 0 micrometer, or a range consisting of any two of the above values.

[0104] In addition, the phosphorus content of the copper foil at the first surface is 499 μg / dm 2 Below, for example 499μg / dm 2 , 490μg / dm 2 , 480μg / dm 2 , 470μg / dm 2 , 460μg / dm 2 , 450μg / dm 2 , 440μg / dm 2 , 430μg / dm 2 , 420μg / dm 2 , 410μg / dm 2 , 400μg / dm 2 、390μg / dm 2 、380μg / dm 2 、370μg / dm 2 , 360μg / dm 2 、350μg / dm 2 、340μg / dm 2 、330μg / dm 2 、320μg / dm 2 、310μg / dm 2 、300μg / dm 2, 290μg / dm 2 , 280μg / dm 2 , 270μg / dm 2 , 260μg / dm 2 , 250μg / dm 2 , 240μg / dm 2 , 230μg / dm 2 , 220μg / dm 2 , 210μg / dm 2 , 200μg / dm 2 , 190μg / dm 2 , 180μg / dm 2 , 170μg / dm 2 , 160μg / dm 2 , 150μg / dm 2 , 140μg / dm 2 , 130μg / dm 2 , 120μg / dm 2 , 110μg / dm 2 , 100μg / dm 2 , 90μg / dm 2 、80μg / dm 2 , 70μg / dm 2 、60μg / dm 2 , 50μg / dm 2 , 40μg / dm 2 , 30μg / dm 2 , 20μg / dm 2 , 10μg / dm 2 , or 0 μg / dm 2 , or a range between any two of the above values. In a preferred embodiment of the present invention, the phosphorus content of the copper foil at the first surface is 199 μg / dm 2 the following.

[0105] The test method for the phosphorus content is as follows. First, cut the copper foil into test samples of 10 cm x 10 cm, and use transparent tape to cover the non-measurement surface (i.e., the second surface other than the first surface). Next, place the test sample flat in a glass container with the first surface facing up, pour in 100 ml of a 21% by weight nitric acid solution (composition: nitric acid and water), and confirm that the liquid surface has submerged the test sample. After soaking at room temperature for 30 seconds, take out the test sample, and use ICP (inductively coupled plasma) emission analysis to analyze and measure the phosphorus content in the nitric acid solution. Three test samples are tested according to the above method and the average value is taken to obtain the phosphorus content on the surface of the copper foil.

[0106] The thickness of the copper foil is not particularly limited, but is preferably 8 μm to 25 μm, such as 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, or 25 μm, or a range between any two of the above values. The thickness of the copper foil is the weight average thickness, that is, the weight per unit area of ​​the copper foil (g / m 2 (g / m2) divided by the copper foil density (g / m 3 (g / m3)) obtained by weight average thickness.

[0107] 1.3.3. Preparation of copper foil

[0108] The method for making the copper foil of the present invention includes but is not limited to the following. First, prepare a copper ion (Cu) containing 65 g / L (grams / liter) to 100 g / L. 2+ ), sulfuric acid (H2SO4) with a concentration of 85g / L to 105g / L, and chloride ions (Cl - Then, the copper electrolyte is passed into a raw foil electrolysis device equipped with a rotatable cathode roller and an insoluble anode, and a current density of 30A / dm is applied to the cathode roller and the insoluble anode respectively. 2 (ampere / square decimeter) to 60A / dm 2The copper electrolyte is then kept at a temperature of 50°C to 58°C and continuously rolled up on a roller to obtain a very low profile (VLP) raw foil. Next, the VLP raw foil is sequentially fed into a continuous surface treatment device via a plurality of guide rollers at a conveying speed of 10 m / min. The continuous surface treatment device includes a roughening treatment tank 1, a roughening treatment tank 1A, a curing treatment tank 2, a curing treatment tank 3, a roughening treatment tank 4, a roughening treatment tank 5, a curing treatment tank 6, a curing treatment tank 7, a nickel plating treatment tank 8, a zinc plating treatment tank 9, an acid treatment tank 10, a pure water treatment tank 10A, and a silane treatment tank 11. In some embodiments of the present invention, the roughening treatment tank 1, the roughening treatment tank 1A, the solidification treatment tank 2, the solidification treatment tank 3, the roughening treatment tank 4, the roughening treatment tank 5, the solidification treatment tank 6, the solidification treatment tank 7, and the nickel plating treatment tank 8 are not energized, and only the zinc plating treatment tank 9, the acid treatment tank 10, the pure water treatment tank 10A, and the silane treatment tank 11 are energized. In other words, the VLP raw foil is only immersed in the solution (e.g., electroplating solution) of each treatment tank without being subjected to relevant treatment when passing through the roughening treatment tank 1, roughening treatment tank 1A, curing treatment tank 2, curing treatment tank 3, roughening treatment tank 4, roughening treatment tank 5, curing treatment tank 6, curing treatment tank 7, and nickel plating treatment tank 8 without being energized, and the VLP raw foil is subjected to relevant treatment only when passing through the galvanizing treatment tank 9, acid treatment tank 10, pure water treatment tank 10A, and silane treatment tank 11 with power on, so the VLP raw foil is subjected to one galvanizing treatment, one chromic acid treatment, one pure water treatment, and one silane treatment. Thus, a non-roughening electrolytic copper foil with a thickness of 18 mm and a first surface Rz of less than 0.5 μm is obtained, that is, the copper foil of the present invention. The parameters of the continuous surface treatment tank are listed in Table 1-1 and Table 1-2, wherein the treatment solution used in treatment tank 11 is a solution containing (3-glycidoxypropyl)trimethoxysilane as a silane coupling agent, the concentration of the silane coupling agent is 5 g / L to 7 g / L, and the solvent used to form the treatment solution is water.

[0109] Table 1-1: Parameters of continuous surface treatment tank

[0110]

[0111] *1: In some embodiments of the present invention, the solution in the treatment tank 8 is pure water instead of the electroplating solution.

[0112] Table 1-2: Parameters of continuous surface treatment tank

[0113]

[0114]

[0115] *2: Examples of trace components include, but are not limited to, Ni, Pd, Ag, and W.

[0116] *3: The tolerance of the treatment tank temperature is ±5°C.

[0117] *4: The error value of current density is ±10%.

[0118] In addition, in the treatment tanks 9, 10, 10A, trace components can be SO4 2- 、HSO4 - PO4 3- 、HPO4 2- 、H2PO4 - The phosphorus content of the first surface of the copper foil can be adjusted by controlling the phosphorus content in the treatment tank 8 and the treatment tank 10 and the water washing amount of the treatment tank 10A. Specifically, the phosphorus content of the first surface of the copper foil can be adjusted by controlling the phosphorus content (in g / L) in the electroplating solution, the water flow rate (in L / s (liters / second)), and the rinsing time (in seconds).

[0119] 1.4. Preparation of copper foil laminate

[0120] The copper foil laminate of the present invention can be prepared as follows. First, a resin sheet is provided as a dielectric layer, and the formation method of the resin sheet is as described above. Next, an adhesive material containing a non-perfluoro resin is provided and the adhesive material is applied to at least one side of the dielectric layer to form an adhesive layer, and the composition of the adhesive material is as described above. After that, a copper foil having the aforementioned properties is provided and the copper foil is arranged on the other side of the adhesive layer opposite to the dielectric layer, thereby obtaining a stack. Finally, the stack is subjected to a hot pressing operation to obtain a copper foil laminate. The conditions of the hot pressing operation can be described as follows. When the dielectric layer contains a thermoplastic resin, at a temperature of 300°C to 450°C and 20kg / cm 2 (kg / cm2) to 40kg / cm 2 Total pressure (initial pressure is 1kg / cm 2 Up to 8kg / cm 2 ) for 5 to 12 hours. When the dielectric layer comprises a thermosetting resin, the temperature is 160 to 300°C and 10 kg / cm 2 Up to 25kg / cm 2 Total pressure (initial pressure is 5kg / cm 2 Up to 12kg / cm 2 ) and hot pressing for 1 to 4 hours.

[0121] 2. Printed Circuit Board

[0122] The copper foil laminate of the present invention can be formed into a printed circuit board by further patterning the copper foil on the outside thereof. Therefore, the present invention also provides a printed circuit board, which is obtained by further patterning the metal foil on the outside of the laminate of the present invention, wherein the method of patterning the metal foil is not particularly limited, and examples thereof include but are not limited to photolithography, screen printing, and inkjet printing.

[0123] 3. Example

[0124] 3.1. Description of measurement method

[0125] The present invention is further illustrated by the following specific embodiments, wherein the measuring instruments and methods used are as follows:

[0126] [Ten-point average roughness (Rz) measurement]

[0127] The ten-point average roughness (Rz) of the copper foil is measured in accordance with the specification of JIS B0601: 2001. The unit of Rz is micrometer.

[0128] [Measurement of surface phosphorus content]

[0129] First, cut the copper foil into 10 cm x 10 cm test samples, and use transparent tape to cover the non-measurement surface (i.e., the second surface other than the first surface). Next, place the test sample flat in a glass container with the first surface facing up, pour in 100 ml of a 21% by weight nitric acid solution (composition: nitric acid and water), and make sure that the solution surface covers the test sample. After soaking at room temperature for 30 seconds, take out the test sample, and use ICP (inductively coupled plasma) emission analysis to analyze and measure the phosphorus content in the nitric acid solution. Test three test samples and take the average value to obtain the phosphorus content on the copper foil surface. The unit of phosphorus content is μg / dm 2 .

[0130] [Tear strength test]

[0131] Tear strength refers to the adhesion of copper foil. Cut the copper foil laminate into 1 / 8 inch width, and then tear the copper foil vertically from the board surface. The strength of adhesion is expressed by the amount of force required. The unit of tear strength is lbf / in (pound force / inch).

[0132] [Heat resistance test]

[0133] Heat resistance is represented by the tear strength of the copper foil laminate after reflow treatment. First, the copper foil laminate is placed in an infrared reflow oven (model: TSK-8000, purchased from Debon Electromechanical Company) and subjected to reflow at 260°C for 10 seconds, which is one reflow treatment. After 10 reflow treatments, the tear strength of the copper foil laminate after reflow treatment is measured by the method described in the aforementioned "Tear Strength Test". The unit of tear strength is lbf / in.

[0134] [Anti-aging properties test]

[0135] The anti-aging properties are represented by the tear strength of the copper foil laminate after aging treatment. First, place the copper foil laminate in a dryer at 105°C for 2 hours to remove moisture from the copper foil laminate. Then, take the copper foil laminate out of the dryer and put it in a desiccator to allow the temperature to naturally return to 25°C. Place the dried copper foil laminate in an oven at 177°C for 10 days for aging treatment. Afterwards, measure the tear strength of the copper foil laminate after aging treatment using the method described in the aforementioned "Tear Strength Test". The unit of tear strength is lbf / in.

[0136] 3.2. List of raw materials used in the examples and comparative examples

[0137] Table 2: Raw material information list

[0138]

[0139] 3.3. Preparation of copper foil laminate

[0140] <Dielectric Layer Preparation Example 1>

[0141] 666.67 grams of PTFE dispersion D-210 (PTFE solid content 60% by weight) and 600 grams of filler SC-5500SVC were mixed evenly to form a glue, wherein the filler content was 60% by weight based on the total content of the glue. Then, the glue was further stirred to form a dough-like object, and the dough-like object was subjected to an extrusion molding process to obtain a sheet material. Thereafter, the sheet material was baked at 150° C. to remove moisture and surfactant. Finally, the sheet material was baked at 360° C. for 10 minutes to obtain a PTFE dielectric layer (hereinafter referred to as "PTFE dielectric layer 1") without a reinforcement material, and the thickness was 254 microns.

[0142] <Dielectric Layer Preparation Example 2>

[0143] 1333.33 g of PTFE dispersion D-210 (PTFE solid content 60 wt%) and 200 g of filler SC-5500SVC were mixed evenly to form a glue, wherein the filler content was 20 wt% based on the total content of the glue. Next, 1080 type E-glass fiber cloth (thickness 60 μm) was prepared and impregnated twice in the glue so that a sufficient amount of resin adhered to the E-glass fiber cloth. Thereafter, the impregnated E-glass fiber cloth was baked at 360° C. for 10 minutes to obtain a PTFE dielectric layer containing a reinforcing material (hereinafter referred to as "PTFE dielectric layer 2") having a thickness of 254 μm.

[0144] <Dielectric layer preparation example 3>

[0145] 50.0 g of polyphenylene ether SA9000, 50.0 g of TAIC, 10.0 g of elastomer Ricon 100, 1.0 g of catalyst Perbutyl P and 100.0 g of filler SC-5500SVC were mixed at room temperature using a stirrer, and methyl ethyl ketone (purchased from Genxiang Industrial Co., Ltd.) and toluene (purchased from Sichuan Qing Chemical Co., Ltd.) were added. Then, the resulting mixture was stirred at room temperature for 60 to 120 minutes to obtain a polyphenylene ether resin composition. After that, 1080 type E-glass fiber cloth (thickness 64 microns) was prepared and impregnated in the polyphenylene ether resin composition, and the impregnated E-glass fiber cloth was baked at 175°C for 2 minutes to obtain a PPE dielectric layer containing a reinforcement material (hereinafter referred to as "PPE dielectric layer"), the thickness of which was 254 microns.

[0146] <Dielectric Layer Preparation Example 4>

[0147] 13.0 g of epoxy resin BNE-210, 25.0 g of dicyandiamide Dicy, 15.0 g of bismaleimide BMI-70, 0.01 g of catalyst 2MI and 30.0 g of SiO2 filler SC-5500SVC were mixed at room temperature using a stirrer, and methyl ethyl ketone (purchased from Genxiang Industrial Co., Ltd.) was added. Then, the resulting mixture was stirred at room temperature for 60 to 120 minutes to obtain an epoxy resin composition. After that, 1080 type E-glass fiber cloth (thickness 64 microns) was prepared and impregnated in the epoxy resin composition, and the impregnated E-glass fiber cloth was baked at 175°C for 2 minutes to obtain an epoxy dielectric layer containing a reinforcing material (hereinafter referred to as "epoxy dielectric layer"), the thickness of which was 254 microns.

[0148] <Copper Foil Preparation Example>

[0149] First, prepare a solution containing 65 g / L to 100 g / L of copper ions (Cu 2+ ), sulfuric acid (H2SO4) with a concentration of 85g / L to 105g / L, and chloride ions (Cl- Then, the copper electrolyte is passed into a raw foil electrolysis device equipped with a rotatable cathode roller and an insoluble anode, and a current density of 30A / dm is applied to the cathode roller and the insoluble anode respectively. 2 (ampere / square decimeter) to 60A / dm 2 After that, the copper electrolyte is kept at a temperature of 50°C to 58°C and continuously rolled up on a roller to obtain a VLP raw foil with a copper purity of 99.9%.

[0150] Next, the VLP green foil was sequentially fed into a continuous surface treatment device via a plurality of guide rollers at a conveying speed of 10 m / min, and the VLP green foil was surface treated according to the conditions shown in Table 3-1, Table 3-2, and Table 3-3 to obtain copper foils 1 to 10. The Rz and phosphorus content of the first surfaces of copper foils 1 to 10 were measured according to the above method and recorded in Table 3-1, Table 3-2, and Table 3-3.

[0151] Table 3-1: Processing conditions and properties of copper foils 1 to 4

[0152]

[0153]

[0154] Table 3-2: Processing conditions and properties of copper foils 5 to 8

[0155]

[0156] *5: When treating the copper foil 8, the solution in the treatment tank 8 is pure water instead of the electroplating solution.

[0157] Table 3-3: Processing conditions and properties of copper foils 9 and 10

[0158]

[0159]

[0160] <Adhesion Layer Preparation Example 1>

[0161] 40.0 g of non-perfluorinated resin SE-405 and 4.0 g of PFOA were mixed with a stirrer at room temperature, and water was added as a solvent. Then, the obtained mixture was stirred at a rotation speed of 700 rpm for 15 to 20 minutes at room temperature to obtain an adhesive material. Thereafter, the adhesive material was coated on the first surface of the copper foil, and the copper foil coated with the adhesive material was placed in an oven and baked at 160° C. for 3 minutes. Then, the baked copper foil was taken out and allowed to cool naturally to room temperature, and then placed in a nitrogen oven and sintered at 380° C. for 15 minutes to obtain an adhesive layer 1 formed on the copper foil, and the thickness of the adhesive layer 1 was 6 microns.

[0162] <Adhesion Layer Preparation Example 2>

[0163] 40.0 g of non-perfluororesin GK-570 and 4.0 g of PFOA were mixed with a stirrer at room temperature, and toluene was added as a solvent. Then, the obtained mixture was stirred at a speed of 700 rpm at room temperature for 15 to 20 minutes to obtain an adhesive material. Thereafter, the adhesive material was coated on the first surface of the copper foil, and the copper foil coated with the adhesive material was placed in an oven and baked at 160° C. for 3 minutes. Then, the baked copper foil was taken out and allowed to cool naturally to room temperature, and then placed in a nitrogen oven and sintered at 380° C. for 15 minutes to obtain an adhesive layer 2 formed on the copper foil, and the thickness of the adhesive layer 2 was 6 microns.

[0164] <Adhesion Layer Preparation Example 3>

[0165] 40.0 g of perfluororesin D210 and 4.0 g of PFOA were mixed with a stirrer at room temperature, and water was added as a solvent. Then, the obtained mixture was stirred at a rotation speed of 700 rpm at room temperature for 15 to 20 minutes to obtain an adhesive material. Thereafter, the adhesive material was coated on the first surface of the copper foil, and the copper foil coated with the adhesive material was placed in an oven and baked at 160° C. for 3 minutes. Then, the baked copper foil was taken out and allowed to cool naturally to room temperature, and then placed in a nitrogen oven and sintered at 380° C. for 15 minutes to obtain an adhesive layer 3 formed on the copper foil, and the thickness of the adhesive layer 3 was 6 microns.

[0166] <Adhesion Layer Preparation Example 4>

[0167] 40.0 g of perfluororesin 335D and 4.0 g of PFOA were mixed with a stirrer at room temperature, and water was added as a solvent. Then, the obtained mixture was stirred at a rotation speed of 700 rpm for 15 to 20 minutes at room temperature to obtain an adhesive material. Thereafter, the adhesive material was coated on the first surface of the copper foil, and the copper foil coated with the adhesive material was placed in an oven and baked at 160° C. for 3 minutes. Then, the baked copper foil was taken out and allowed to cool naturally to room temperature, and then placed in a nitrogen oven and sintered at 380° C. for 15 minutes to obtain an adhesive layer 4 formed on the copper foil, and the thickness of the adhesive layer 4 was 6 microns.

[0168] <Preparation of Copper Foil Laminated Board>

[0169] According to the compositions of Table 4-1 to Table 4-3, the copper foil laminates of Examples 1 to 48 and Comparative Examples 1 to 68 were prepared in the following manner. First, several dielectric layers were laminated, and a 0.5 ounce copper foil with an adhesive layer formed thereon was laminated on the outermost layers on both sides, and then placed in a hot press for high-temperature hot pressing and curing. The conditions for the hot pressing operation are as follows. When the dielectric layers are PTFE dielectric layer 1 and PTFE dielectric layer 2, the temperature was raised to 380°C at a heating rate of 5°C / min to 10°C / min, and at this temperature, the temperature was heated at 30kg / cm 2 Total pressure (initial pressure is 5kg / cm 2 ) and hot pressing for 7 to 9 hours. When the dielectric layer is a PPE dielectric layer and an epoxy dielectric layer, the temperature is raised to 200 to 220°C at a heating rate of 2 to 4°C / min and at this temperature at a speed of 18kg / cm 2 Total pressure (initial pressure is 8kg / cm 2 The tear strength, heat resistance and anti-aging properties of the copper foil laminates of Examples 1 to 48 and Comparative Examples 1 to 68 were tested according to the above methods and recorded in Tables 5-1 to 5-4.

[0170] Table 4-1: Composition of copper foil laminates of Examples 1 to 48

[0171]

[0172] Table 4-2: Composition of copper foil laminates of Comparative Examples 1 to 48

[0173]

[0174]

[0175] Table 4-3: Composition of copper foil laminates of Comparative Examples 49 to 68

[0176]

[0177] Table 5-1: Properties of copper foil laminates of Examples 1 to 24

[0178]

[0179]

[0180] Table 5-2: Properties of copper foil laminates of Examples 25 to 48

[0181]

[0182] Table 5-3: Properties of copper foil laminates of Comparative Examples 1 to 48

[0183]

[0184]

[0185] Table 5-4: Properties of copper foil laminates of Comparative Examples 49 to 68

[0186]

[0187] As shown in Table 5-1 and Table 5-2, the copper foil laminate of the present invention has good tear strength, heat resistance and aging resistance. Specifically, when the same adhesive layer and the same dielectric layer are used, when the phosphorus content of the first surface of the copper foil is lower, the copper foil laminate has better performance in tear strength, heat resistance and aging resistance. More specifically, when the phosphorus content of the first surface of the copper foil is 199 μg / dm 2 When the temperature is below 500 °C, the obtained copper foil laminate can obtain further improvements in tear strength, heat resistance and aging resistance.

[0188] Different from this, as shown in Tables 5-3 and 5-4, copper foil laminates not of the present invention cannot have good tear strength, heat resistance and aging resistance. Specifically, when the same copper foil and the same dielectric layer are used, when the adhesive layer contains perfluororesin instead of non-perfluororesin, the tear strength of the copper foil laminate is extremely poor. In addition, when the same adhesive layer and the same dielectric layer are used, when the phosphorus content of the first surface of the copper foil is higher than 499μg / dm 2 When the Rz of the first surface of the copper foil is higher than 0.5 μm and the adhesive layer contains a perfluororesin instead of a non-perfluororesin, the heat resistance and aging resistance of the copper foil laminated board are significantly poor.

[0189] The above embodiments are only used to illustrate the principles and effects of the present invention and to illustrate the technical features of the present invention, and are not used to limit the protection scope of the present invention. Any changes or arrangements that can be easily completed by any person skilled in the art without violating the technical principles of the present invention are within the scope claimed by the present invention. Therefore, the scope of protection of the present invention is as listed in the claims.

Claims

1. A copper foil laminate, characterized in that: Include: Dielectric layer; an adhesive layer disposed on at least one side of the dielectric layer and formed of an adhesive material including a non-perfluororesin; and A copper foil having a first surface, the copper foil is disposed on the other side of the adhesive layer opposite to the dielectric layer, and is adhered to the adhesive layer with the first surface. The first surface has a ten-point average roughness of less than 0.5 micrometers, and the phosphorus content of the copper foil at the first surface is less than 499 micrograms / square decimeter.

2. The copper-clad laminate according to claim 1, wherein: The non-perfluororesin has a fluorine atom content of 60% or less based on the total number of atoms in the repeating unit.

3. The copper-clad laminate according to claim 1, wherein: The phosphorus content of the copper foil at the first surface is 199 μg / dm 2 the following.

4. The copper-clad laminate according to any one of claims 1 to 3, wherein: The non-perfluorinated resin is selected from the following group: polychlorotrifluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, ethylene-tetrafluoroethylene copolymer, ethylene-chlorotrifluoroethylene copolymer, and combinations thereof.

5. The copper-clad laminate according to any one of claims 1 to 3, wherein The dielectric layer includes a dielectric material formed from a resin composition.

6. The copper-clad laminate according to claim 5, wherein: The resin composition comprises a thermosetting resin selected from the following group: epoxy resin, thermosetting phenolic resin with reactive functional groups, thermosetting benzoxazine resin, thermosetting polyphenylene ether resin, and combinations thereof.

7. The copper-clad laminate according to claim 5, wherein: The resin composition comprises a thermoplastic resin selected from the group consisting of a perfluororesin, a liquid crystal polymer, and a combination thereof.

8. The copper-clad laminate according to claim 7, wherein: The perfluororesin is selected from the following group: polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and combinations thereof.

9. The copper-clad laminate according to claim 5, wherein: The resin composition further comprises a component selected from the following group: a catalyst, an elastomer, a filler, a dispersant, a toughening agent, a viscosity modifier, a flame retardant, a plasticizer, a coupling agent, and a combination thereof.

10. A printed circuit board, characterized in that: The copper-clad laminate is made from the copper-clad laminate according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Microetching agent for copper or copper alloy and surface treating method using the same

    JP2000282265A

  • Resin composition and uses of the same

    US20160280913A1

  • Curable polyphenylene ether resin composition and a cured resin composition obtainable therefrom

    US5218030A

  • Curable polyphenylene ether and cyanurate resin composition and a cured resin composition obtainable therefrom

    US5352745A

  • Poly(phenylene ether)-polyvinyl thermosetting resin

    US6352782B2